FAMILY PIOPHILIDAE - Wolff, Marta; Pérez, Sandra; Grisales, Diana (Zootaxa, 2016)
Piophilidae is a little family poorly known in Colombia, with only Piophila casei (L.) and Stearibia nigriceps Meigen reported so far. This catalogue expands the distribution of these species to other localities in the country.